Bioactivity of Bacillus thuringiensis (Bacillales: Bacillaceae) on Diatraea saccharalis (Lepidoptera: Crambidae) eggs. Issue 4 (11th January 2021) - Daquila, Bruno V; Dossi, Fábio CA; Moi, Dieison A; Moreira, Daiani R; Caleffe, Ronaldo RT; Pamphile, João A; Conte, Helio
Abstract: BACKGROUND: Bacillus thuringiensis (Bt) is a Gram‐positive bacterium that synthesizes specific protein toxins, which can be exploited for control of various insect pests, including Diatraea saccharalis, a lepidopteran that severely damages sugarcane crops. Although studies have described the effects of Bt in the larval phases of D. saccharalis, few have examined its effect on insect eggs. Herein, we studied the entomopathogenic potential of Bacillus thuringiensis serovar Aizawai GC‐91 (Bta) during D. saccharalis embryo development with the aim of understanding the entomopathogenic mechanism and developing new biological control techniques for target insects. RESULTS: Bta concentrations of 5, 10 and 20 g L –1 demonstrated the strongest bioactivity, reducing D. saccharalis egg viability by 28.69%, 33.91% and 34.98%, respectively. The lethal concentrations (LCs) were estimated as: LC50 = 28.07 g L –1 (CI 95% = 1.89–2.38) and LC90 = 65.36 g L –1 (CI 95% = 4.19–5.26). Alterations in egg coloration, melanization and granule accumulation were observed at 24 h, persisting until 144 h. The embryo digestive systems were severely damaged, including narrowing of the intestinal lumen, vesiculations and degenerated cells, causing embryonic death. CONCLUSION: The toxicity caused by Bta in D. saccharalis embryos demonstrated its potential as a biological control agent and as a sustainable alternative for integrated management of D. saccharalis infestation. © 2020 Society of Chemical Industry Abstract : Bacillus thuringiensis serovar Aizawai GC‐91 (Bta) has demonstrated toxicity during embryonic development of Diatraea saccharalis, indicating that this entomopathogen can be utilized in integrated pest management of the insect. © 2020 Society of Chemical Industry